Neglected and underutilized plant species: Regional report 1999-2000: strategic action plan of the International Plant Genetic Resources Institute - International Plant Genetic Resources Institute (2003)
Global food security and economic growth now depend on a declining number of plant species. This has placed the future supply of food and rural incomes at risk. To fulfil its global mandate to conserve and use the world's plant genetic resources for the development and welfare of present and future generations IPGRI is committed to promoting greater awareness of the important part that 'minor crops' play in securing the livelihoods of people around the world. IPGRI is uniquely suited to this work, thanks to the wide experience it already has of working with neglected and underutilized species. It will focus on four major areas where neglected and underutilized species can contribute to sustainable agriculture: - food security and better nutrition; - increased incomes for the rural poor; - ecosystem stability; - cultural diversity. To reach this goal IPGRI has set out three main objectives: - Develop priority-setting approaches; - Enhance the conservation and use of plant genetic resources of NUS; - Strengthen the efforts of other actors;